Season of delivery and risk of venous thromboembolism during hospitalization among pregnant women - Li, Qian; Wang, Hongfei; Wang, Huafang; Deng, Jun; Cheng, Zhipeng; Lin, Wenyi; Zhu, Ruiqi; Chen, Shi; Guo, Jinrong; Li, Huarong; Chen, Yong; Yuan, Xiaowei; et al. (Frontiers in Public Health, 2023)
Background Season was found to be related to the occurrences of venous thromboembolism (VTE) in hospitalized patients. No prior study had explored whether season was associated with VTE risk in pregnant women. This study aimed to investigate the relationships of season of delivery and VTE risk during hospitalization among pregnant women. Methods This is a multi-center retrospective cohort study of pregnant women. Participants delivered in 7 designated sites in Hubei Province, China, during the period from January 2017 to December 2022. The participants were categorized according to their season/month of delivery. Information on new-onset VTE during hospitalization was followed. Results Approximately 0.28% (104/37778) of the pregnant women developed new-onset VTE during hospitalization for delivery. After adjustment, compared with participants in group of spring, participants in groups of summer, autumn, and winter had increased risk of VTE during hospitalization. The ORs were 2.59 [1.30, 5.15], 2.83 [1.43, 5.60], and 2.35 [1.17, 4.75] for groups of summer, autumn, and winter, respectively. Pregnant women in the combined group (summer + autumn + winter) had increased risk of VTE during hospitalization than those in group of spring (OR, 2.59 [1.39, 4.85]). Restricting the analyses among pregnant women without in vitro fertilization, gestational diabetes mellitus, and preterm, the results still remained robust. Compared with participants delivered in March, April and May, participants delivered in June, July, September, November, December, and February had higher risk of VTE during hospitalization. Conclusions This study demonstrated that pregnant women who delivered in summer, autumn, and winter had increased VTE risk during hospitalization compared with those who delivered in spring.